Speech recognition method and device, electronic equipment and storage medium - BAN ZHIHUA (2024)
The invention relates to the field of voice recognition, in particular to a voice recognition method and device, electronic equipment and a storage medium, and the method comprises the steps: obtaining a current to-be-processed data frame and a context to-be-processed data frame of the current to-be-processed data frame, the context to-be-processed data frame comprises a previous to-be-processed data frame before the current to-be-processed data frame and a next to-be-processed data frame after the current to-be-processed data frame; on the basis of the context to-be-processed data frame, performing preprocessing of increasing a receptive field on the current to-be-processed data frame to obtain a preprocessing result of the current to-be-processed data frame; and according to the pre-processing result, coding and decoding after coding are carried out, and a speech recognition result is determined. Before coding, the context to-be-processed data frame is utilized to perform the preprocessing of increasing the